Money saving guideline for preparations to retirement of the population in The Central Regional - Teerakittikon, Thanawut; Woenthong, Somsri (Journal of Industrial Business Administration, 2020)
The purpose of this research was to study money saving guideline for preparations to retirement of the population in the central regional. The population in the central regional who is an employee registered with the Social Security Department 2,540,672 persons (Social Security Department, 2019) were targeted of this research with sample size 400 persons. SPSS program used to statistical analysis with statistical significance at the level of 0.05. The results have been showed that most respondent is female who respondents more than males, the age within 41-50 years, marital status, bachelor degree and 3-4 family members. The opinions on the importance level of money saving guideline for preparations to retirement in the central regional in overall at a high level. When classified in each aspect has found that the pattern of saving money and the attitude of saving money has the importance at a medium level. Financial literacy has the importance at a low level. The comparison of differences by personal status has been found that the education was significantly different at the level of 0.05. The comparison of gender, age, marriage status, and family member found that no significant difference at the level of 0.05.